MODELING THE DURATION OF MATERNAL LABOR AT ANUTAPURA HAMMER HOSPITAL USING LIN-YING ADDITIVE HAZARD REGRESSION - Fadjryani Fadjryani; Iman Setiawan; Hartayuni Sain; Mohammad Fajri; Nurul Fiskia Gamayanti; Aryani Radi; Cici Aisya (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
The Central Sulawesi government has a Sustainable Development Goals (SDGs) target for 2020-2024, which sets the maternal mortality rate below 70/100,000 KH. However, in 2018-2022, the maternal mortality rate fluctuated by 128/100,000 KH. One of the factors causing maternal mortality is the duration of the labor process. The factors that are thought to have an influence on the duration of labor are gestational age, maternal age, baby height, parity, and hemoglobin levels. Therefore, this study aims to see what modeling and factors affect the duration of birth using Lin-Ying additive hazard regression analysis. Data were obtained from the medical records of normal deliveries between January and December 2023 at Anutapura Palu Hospital. The results showed that the factors that affect the duration of birth are preterm gestational age, aterm gestational age, maternal age 20-35 years, primigravida mothers, multigravida mothers, and mothers who are not anemic. A limitation of this study is the relatively short data collection period of one year, which may not capture variations or trends in labor outcomes over time.